Exposure systems used in the assessment of emf impact on living organisms - Cala, Pawel; Bienkowski, Pawel (НТУ "ХПІ", 2017)
The subject of the study in the article is the processes of analysis and exposure assessment of electromagnetic field on humans. The main goal is to optimize size of the exposure antenna systems, its electrical parameters and generated electromagnetic field (EMF) for different frequency range. Objectives: Electromagnetic field (EMF – Electromagnetic Fields) studies on living organisms are one of the important branches of biomedical research. Most of this type of research is conducted using dedicated exposures system with fixed and controlled EMF exposure conditions. The purpose of biomedical research is to determine the influence of electromagnetic fields on living organisms. For this purpose the exposure systems are designed. The main task of the exposure antenna system, is to produce the EMF with known and controlled parameters in a specific EMF area. Depending on the frequency and the component (E or H) of the electromagnetic field used, different types of systems are used. For low frequencies (for instance 50 Hz common frequency) and magnetic fields, Helmholtz solenoids or coils are used, and for electric fields - flat capacitors (E Field). For higher frequencies field E is used for systems with linear antennas or TEM lines. There are also dedicated probes for invasive tissue heating. Each solution has its advantages and limitations and usually there are no universal solutions for all cases. Results: For the generation of a low frequency magnetic field up to several hundred Hz, the Helmholtz solenoid or coil is generally used because of its relatively simple construction, the ability to obtain high intensity and good homogeneity of the field in a relatively large area relative to the dimensions of the whole system. The homogeneous field area can be determined analytically based on system geometry or measurement. Otherwise it looks for exposure system above few MHZ. To create a homogeneous EMF in the field of radio frequencies, the exposure systems - usually the TEM lines (Crawford compartment) or sometimes the GTEM are very likely to be used. In both cases there are frequency and spatial limitations - the homogeneous field is assumed to be maximally present. At 1/3 the height between the plates of the chamber and at the same time the maximum frequency of operation of the TEM chamber can be described by the approximate dependence of fmax [MHz] = 50 / d [m], resulting in a chamber operating at 1 GHz. The work piece does not exceed a height of about 1.5 cm with a diameter of about 4 cm. Larger working areas, but at the same time, a lower homogeneity of the field can be obtained in the GTEM chamber - but at the same time the GTEM chamber has much larger geometric dimensions. Another way is to produce PEM with the parameters in open space - in the vicinity of the antenna. In this case, it is very important to select an antenna so that the expected homogeneous area can be obtained at an acceptable distance from the antenna - in order to maintain high EMF intensity and to reduce the radiation of the antenna beyond the desired area. This can be achieved by limiting the emission area by, for example, shielding or using EMF absorbers. In addition authors simulate novel ablation antenna for ablation treatment. Conclusions: Assessing the impact of EMF on biological objects is an interdisciplinary studies that requires the involvement of biological or medical specialists, as well as the EMF standard field and metrology specialist. In this work we have taken the subject of correct selection and description used in the experience of exposure systems. The authors presented the most commonly used EMF emitters in the low frequencies and microwave bands, as well as new model of the ablation treatment antenna.

Предметом дослідження є процеси аналізу та оцінки впливу електромагнітного поля на людей. Мета - оптимізувати розмір антенних систем експонування, їх електричних параметрів і генералізованого електромагнітного поля (ЕМП) для різних частотних діапазонів. Завдання: дослідження дії електромагнітного поля на живі організми. Дане дослідження є однією з важливих галузей біомедичних досліджень. Велика частина цього типу досліджень проводиться з використанням спеціальної системи експозиції з фіксованими та контрольованими умовами експозиції ЕМП. Метою біомедицинських досліджень є визначення впливу електромагнітних полів на живі організми. Для цього розроблені системи експозиції. Основна задача системи антенного експонування полягає в створенні ЕМП з відомими та контрольованими параметрами в конкретній області ЕМП. В залежності від частоти та компоненту використовуваного електромагнітного поля використовуються різні типи систем. Для низьких частот і магнітних полів використовуються соленоїди або котушки Гельмгольца, а для електричних полів – плоскі конденсатори. Для більш високих частот поля використовується система з лінійними антенами. Існують також спеціальні пробники для інвазивного нагрівання тканини. Кожне рішення має свої переваги та обмеження, та для всіх випадків немає універсальних рішень. Результати. Для генерації низькочастотного магнітного поля звичайно використовують котушки Гельмгольца із-за їхньої відносно простої конструкції, здатності отримувати високу інтенсивність та хорошу однорідність поля у відносно великій відносній площі до розмірів всієї системи. Область однорідного поля може бути визначена аналітично на основі геометрії або вимірювання системи. В протилежному випадку відбувається пошук системи експозиції вище декількох мГц. Існують частотні та просторові обмеження – припускається, що однорідне поле максимально присутнє. Дуже важливо обрати антену так, щоб очікувана однорідна область могла бути отримана на прийнятній відстані від антени – для підтримки високої інтенсивності ЕМП та зменшення випромінювання антенних сигналів за межами бажаної області. Це може бути досягнуто шляхом обмеження площі викидів, наприклад, шляхом екранізації або використання поглиначів ЕМП. Крім того, автори моделюють нову абляційну антенну для лікування абляції. Висновки. Оцінка впливу ЕМП на біологічні об'єкти є міждисциплінарним дослідженням, яке вимагає участі біологічних або медичних спеціалістів, а також спеціаліста з електромагнітних полів та метрології. В роботі розглядається питання правильного вибору та опису, використаного при експерименті систем експонування. Автори представили найбільш часто використовувані емітери ЕМП в низкочастотних та мікрорівневих діапазонах, а також нову модель антен обробки аблації.
Системи експозиції, що використовуються для оцінки впливу електромагнітного поля на живі організми
Keywords: antenna; exposure systems; frequency; electromagnetic field; антена; системи експозиції; частота; електромагнітне поле